The workstation data link. - Adrian, Merv (New York, United States of America : Multiscience Press, Inc., McGraw-Hill book Company, 1988)
"Surveying the mass of conflicting software standards and hardware incompatibilities that arise when interfacing between microcomputers and mainframes, this applications-oriented guide provides you, the professional user, with the practical information necessary to transfer many types of data files between small and large systems. In three comprehensive sections, it fully explains. * File transfer from the micro side - asynchronous parameters, hardware, and software • protocols for asynch error checking • KERMIT • synchronous communications hardware • micro preprocessing • micro postprocessing * File transfer from the mainframe side - SNA • VTAM, TCAM, and others • teleprocessing monitors • the 3270 protocol • hardware • protocols • data extraction • non-IBM architectures • product approaches * The management perspective - the micro explosion • corporate data architectures • fourth generation languages • the use of data • evaluating the options • functional model of the micro to mainframe link • a manager's checklist for implementation. Since the free exchange of data is one of the major obstacles to the integration of microcomputers into the corporate world, this - state-of-the-art guide to data transfer in a business environment will be one that every professional who deals with corporate data will want to own." (Copied from the past).
Preface. Part one: Models and mainframes. Part two: Movements and micros. Part three: Managing methodologies. Glossary. Index.
Keywords: DATA TRANSFER; HARDWARE; COMPUTERS; ELECTRICAL INTERCONNECTION SYSTEMS -- AUTOMATION; MICROCOMPUTER WORKSTATIONS; COMPUTER NETWORKS; DATA TRANSMISSION SYSTEMS